A method for preparing unfired zirconia fiber-based porous ceramics

By using the soluble crustacin-boric acid-hydroxyxane-silicon powder compound adhesive to combine with oxidation fiber, and use a low temperature drying process, to prepare a porous ceramic ceramics without fiber-free fiber fiber, solve the high energy consumption caused by high temperature sintering. The problem of low intensity of the medium temperature segment realizes ceramic materials with good mechanical properties in each temperature segment.

CN118851754BActive Publication Date: 2025-01-28SHANGHAI ZIXUYANG HIGH TECH MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411339944.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-28
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing preparation methods for zirconia fiber-based porous ceramics require high temperature sintering, resulting in high production energy consumption and low strength of samples in the medium temperature section, so they cannot be directly applied.

Method used

The soluble crustacin-boric acid-hydroxylsilane-silicon powder is used as a composite adhesive. After mixing the ball mill, it is combined with oxidized fiber, and the wind-drum drying box is used for low temperature drying to avoid high temperature sintering.

Benefits of technology

Successfully prepared a burn -free oxidized fiber -based porous ceramic with good mechanical properties in each temperature segment, which solved the problem of high energy consumption and low medium temperature segment caused by high temperature sintering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118851754B_ABST
    Figure CN118851754B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of zirconia fiber-based porous ceramics, and discloses a method for preparing a non-fired zirconia fiber-based porous ceramic, including: using boric acid, soluble chitin, water, polyhydroxy silane and silicon powder to prepare a composite binder slurry; adding zirconia fiber to the composite binder slurry, stirring evenly and transferring it to a mold, and using a polyvinyl chloride film to coat the mold, then transferring it to a blast drying oven to heat and promote the reaction, removing the polyvinyl chloride film, vacuum filtering, obtaining a zirconia fiber-based porous ceramic wet blank, drying it in a blast drying oven, and obtaining a non-fired zirconia fiber-based porous ceramic after demoulding. The present invention uses soluble chitin-boric acid-polyhydroxy silane-silicon powder as a composite binder, and successfully prepares a non-fired zirconia fiber-based porous ceramic with good mechanical properties when used in each temperature range, thereby greatly reducing the production energy consumption required for preparing zirconia fiber-based porous ceramics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of zirconia fiber-based porous ceramics, and in particular relates to a method for preparing firing-free zirconia fiber-based porous ceramics. Background Art

[0002] Porous zirconia ceramics have high porosity, high temperature stability, good biocompatibility, high mechanical strength and excellent chemical inertness, and are widely used in medical, industrial and high-tech fields, such as high temperature insulation materials, high temperature filtration materials, catalyst carriers, biomedical materials, etc. Among the many types of zirconia ceramics, zirconia fiber-based porous ceramics are a type of porous ceramics made from zirconia fiber as the main raw material. It combines the advantages of zirconia fiber and porous ceramics, has lower density and better thermal insulation properties, and is widely used in various thermal insulation systems.

[0003] At present, the main preparation methods of zirconia fiber-based porous ceramics are as follows: first, the zirconia fibers and a certain binder (silica sol, aluminum sol and zirconium sol, etc.) are dispersed in a solvent; then, appropriate ceramic molding processes, such as vacuum filtration, molding, etc., are used to fix the randomly overlapped zirconia fibers, and a stable three-dimensional network structure is formed under the action of the binder. Finally, under high-temperature sintering, the added inorganic sol-like substances will be transformed into more high-temperature resistant ceramics, thereby obtaining zirconia fiber-based porous ceramics with better heat resistance and higher strength. At present, the sintering temperature of zirconia fiber-based porous ceramics is generally above 1000 degrees. This is mainly because the inorganic sol (silica sol, aluminum sol, zirconium sol, etc.) has poor adhesion to zirconia fibers at room temperature and below 1000 degrees, resulting in low strength of the sample and cannot be used normally. Especially at 400-1000 o In the middle temperature range of C, the polymer network structure formed by the inorganic sol during solidification has decomposed, but has not yet transformed into its corresponding oxides (such as silicon oxide, aluminum oxide, zirconium oxide, etc.), which results in the strength of the zirconia fiber-based porous ceramics generated at this time being almost zero. In recent years, with the proposal of the dual-carbon strategy, how to further reduce the sintering temperature for preparing zirconia fiber-based porous ceramics, thereby reducing its production energy consumption, has become the focus of research by scientific researchers. The main purpose of high-temperature sintering is to promote the ceramicization of the inorganic binder inside the zirconia fiber-based porous ceramics, thereby increasing the strength of the sample to meet subsequent application requirements. Therefore, if a zirconia fiber-based porous ceramic with good mechanical strength at different temperatures can be prepared, the high-temperature sintering step can be omitted, thereby obtaining a new type of zirconia fiber-based porous ceramic that does not require firing. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a fire-free zirconia fiber-based porous ceramic. Using soluble chitosan-boric acid-polyhydroxysilane-silicon powder as a composite binder, a fire-free zirconia fiber-based porous ceramic with good mechanical properties in all temperature ranges is successfully prepared, thereby overcoming the high sintering temperature and high energy consumption required for zirconia fiber-based porous ceramics in the prior art.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a calcined zirconia fiber-based porous ceramic comprises the following steps:

[0007] (1) Adding boric acid and soluble chitosan to water, stirring until the boric acid and soluble chitosan are completely dissolved, then adding polyhydroxy silane to the solution, mixing evenly to obtain an organic-inorganic composite solution, wherein the mass ratio of water, boric acid, soluble chitosan and polyhydroxy silane is 100:(1-5):(4-15):(10-20);

[0008] (2) adding silicon powder to the organic-inorganic composite solution, and mixing by ball milling to obtain a composite binder slurry, wherein the mass ratio of the silicon powder to the organic-inorganic composite solution is (1-5):100;

[0009] (3) Adding zirconia fiber to the composite binder slurry, stirring evenly to form zirconia fiber slurry;

[0010] (4) The zirconia fiber slurry is transferred to a mold and the mold is coated with a polyvinyl chloride film. Subsequently, the mold is transferred to a blast drying oven for heating to further promote the reaction between the soluble chitin, boric acid, and polyhydroxy silane; then, the polyvinyl chloride film is removed, and the excess water in the mold is drained by a vacuum filtration process to obtain a zirconia fiber-based porous ceramic wet blank;

[0011] (5) The obtained zirconia fiber-based porous ceramic wet blank is dried in a forced air drying oven, and after demolding, a firing-free zirconia fiber-based porous ceramic is obtained.

[0012] Furthermore, the mass ratio of water, boric acid, soluble chitosan and polyhydroxysilane is 100:(3-5):(6-10):(15-20).

[0013] Furthermore, the mass ratio of the silicon powder and the organic-inorganic composite solution in step (2) is (1-3):100.

[0014] Furthermore, the mass ratio of the zirconium oxide fiber and the composite binder slurry in step (3) is (2-5):100.

[0015] Furthermore, the temperature of the blast drying oven in step (4) is 60-80° C., and the insulation time is 3-6 h.

[0016] Furthermore, the temperature of the blast drying oven in step (5) is 80-90° C., and the insulation time is 6-8 h.

[0017] In view of the high sintering temperature and serious energy consumption required for the current zirconia fiber-based porous ceramics, the present application proposes to use zirconia fiber as the matrix and soluble chitosan-boric acid-polyhydroxysilane-silicon powder as an organic-inorganic composite binder to prepare a kind of zirconia fiber-based porous ceramics with good mechanical properties in all temperature ranges. First of all, soluble chitosan has a high molecular weight, contains amino, acetylamino and hydroxyl groups, and is tightly combined with zirconia fiber, which can significantly improve the room temperature strength of zirconia fiber-based porous ceramics. However, soluble chitosan is essentially a polymer material with poor temperature resistance. It will slowly decompose above 300°C, resulting in a decrease in the mechanical properties of the material. For this reason, the present application uses boric acid to modify soluble chitosan. Boric acid generates borate ions in water, which can react with the hydroxyl groups of soluble chitosan by condensation. At this time, the soluble chitosan is cross-linked by borate ions to form a more complex network structure linked by BOC bonds. This complex network structure can effectively improve the temperature resistance of soluble chitin and its bonding strength at low temperatures (room temperature to 400 o C). In addition, the present application also introduces polyhydroxy silane into the slurry. Compared with the CC main chain of soluble chitin, the main chain of polyhydroxy silane is Si-O-Si bond, which has higher temperature resistance, and the hydroxyl groups it carries can also undergo condensation reaction with borate ions to form a three-dimensional network structure with Si-OB as the main network. Therefore, when the temperature reaches the decomposition temperature of soluble chitin, polyhydroxy silane can be used as a replacement material to continue to ensure the strength of zirconia fiber-based porous ceramics (400-600 o C). When the temperature continues to rise (600-1000 o C), It will decompose with polyhydroxy silane, and the generated BO bonds and Si-O bonds will further generate low-melting-point borosilicate glass, thereby continuing to ensure the strength of zirconia fiber-based porous ceramics. o C. Borosilicate glass will soften, but the added silicon powder will oxidize to generate active silicon oxide. Silicon oxide can increase the temperature resistance of the overall binder, thereby ensuring that the zirconia fiber-based porous ceramics also have excellent strength at high temperatures.

[0018] The advantages and positive effects of the present invention are:

[0019] The present invention uses soluble chitosan-boric acid-polyhydroxysilane-silicon powder as a composite binder and zirconia fiber as a raw material to prepare a zirconia fiber-based porous ceramic that has good mechanical properties when used in various temperature ranges. The polymerization reaction of boric acid with soluble chitosan and polyhydroxysilane ensures that the zirconia fiber-based porous ceramic can be used at 600 o C, and the borosilicate glass formed by boric acid, polyhydroxy silane and silicon powder ensures that the zirconia fiber-based porous ceramics have good strength at 600 o C and above have better strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM image of the unfired zirconia fiber-based porous ceramic prepared in Example 1, magnified 300 times;

[0021] Figure 2 This is a SEM image of the unfired zirconia fiber-based porous ceramic prepared in Example 2, magnified 300 times. DETAILED DESCRIPTION

[0022] In order to better understand the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings. In the case of no conflict, the features in the case can be combined with each other. The raw materials used in the following examples are all commercially available analytically pure raw materials.

[0023] Example 1

[0024] A method for preparing a calcined zirconia fiber-based porous ceramic comprises the following steps:

[0025] (1) Add 5 g of boric acid and 10 g of soluble chitosan to 100 g of water, stir until the boric acid and soluble chitosan are completely dissolved, then add 20 g of polyhydroxysilane (purchased from Guangdong Biaomei Silicon Fluorine New Materials Co., Ltd., model K-363B) to the solution, mix well to obtain an organic-inorganic composite solution;

[0026] (2) Add 4 g of silicon powder to the organic-inorganic composite solution and mix them evenly by ball milling to obtain a composite binder slurry;

[0027] (3) Add 4g of zirconia fiber to the composite binder slurry, stir evenly and add the zirconia fiber slurry;

[0028] (4) The zirconia fiber slurry is transferred to a mold and the mold is coated with a polyvinyl chloride film. Subsequently, the mold is transferred to a blast drying oven and heated at 70° C. for 4 h to remove the polyvinyl chloride film. The excess water in the mold is drained by a vacuum filtration process to obtain a zirconia fiber-based porous ceramic wet blank.

[0029] (5) The obtained zirconia fiber-based porous ceramic wet blank is transferred to a forced air drying oven, kept at 85°C for 6 hours, and then demolded to obtain the unfired zirconia fiber-based porous ceramic.

[0030] The scanning electron microscope image of the unfired zirconia fiber-based porous ceramic prepared in Example 1 is as follows: Figure 1 shown.

[0031] Example 2

[0032] A method for preparing a calcined zirconia fiber-based porous ceramic comprises the following steps:

[0033] (1) Add 4 g of boric acid and 8 g of soluble chitosan to 100 g of water, stir until the boric acid and soluble chitosan are completely dissolved, then add 17 g of polyhydroxysilane (purchased from Guangdong Biaomei Silicon Fluorine New Materials Co., Ltd., model K-363B) to the solution, mix well to obtain an organic-inorganic composite binder solution;

[0034] (2) Add 3 g of silicon powder to the organic-inorganic composite solution and mix them evenly by ball milling to obtain a composite binder slurry;

[0035] (3) Add 5g of zirconia fiber to the composite binder slurry, stir evenly and add the zirconia fiber slurry;

[0036] (4) The zirconia fiber slurry is transferred to a mold and the mold is coated with a polyvinyl chloride film. Subsequently, the mold is transferred to a blast drying oven and heated at 75° C. for 3 h to remove the polyvinyl chloride film. The excess water in the mold is drained by a vacuum filtration process to obtain a zirconia fiber-based porous ceramic wet blank.

[0037] (5) The obtained zirconia fiber-based porous ceramic wet blank is transferred to a forced air drying oven, kept at 90°C for 7 hours, and then demolded to obtain the unfired zirconia fiber-based porous ceramic.

[0038] The scanning electron microscope image of the unfired zirconia fiber-based porous ceramic prepared in Example 2 is as follows: Figure 2 shown.

[0039] Comparative Example 1

[0040] A method for preparing a calcined zirconia fiber-based porous ceramic, the preparation method is the same as that of Example 1, except that in step (1), no boric acid is added.

[0041] Comparative Example 2

[0042] A method for preparing a calcined zirconia fiber-based porous ceramic, the preparation method is the same as that of Example 1, except that in step (1), 5 g of boric acid and 10 g of soluble chitosan are added to 100 g of water, stirred until the boric acid and the soluble chitosan are completely dissolved, and then 20 g of silica sol is added to the solution, and mixed evenly to obtain an organic-inorganic composite solution.

[0043] Comparative Example 3

[0044] A method for preparing a calcined zirconia fiber-based porous ceramic is disclosed. The preparation method is the same as that of Example 1, except that step (2) is omitted, that is, silicon powder is not added.

[0045] Evaluation and characterization

[0046] Figure 1 This is a 300-fold magnified SEM image of the unfired zirconia fiber-based porous ceramic prepared in Example 1. Figure 2The SEM image of the unfired zirconia fiber-based porous ceramic prepared in Example 2 is magnified 300 times. It can be seen that the prepared zirconia fiber-based porous ceramic exhibits a three-dimensional skeleton structure formed by overlapping zirconia fibers, and the added composite binder is attached to the intersection of the zirconia fibers to fix the fiber network structure. Table 1 shows the compressive strength of the unfired zirconia fiber-based porous ceramics prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 directly at different test temperatures. It can be seen that for the samples prepared in Example 1 and Example 2, the compressive strength at different test temperatures is greater than 1.0MPa, which ensures that the prepared unfired zirconia fiber-based porous ceramics can be used directly in different temperature scenes. In the designed formula, the role of boric acid is to form a cross-linked network structure with soluble chitin and polyhydroxy silane, thereby increasing the temperature resistance of the two organic substances and increasing the strength of the sample at 400~600℃. In addition, boric acid can also form borate glass with polyhydroxy silane, thereby increasing the strength of the sample at 600~1000℃. Therefore, for Comparative Example 1, since boric acid is not added to its formula, the strength of the overall sample at 400~1000℃ is relatively low, especially at 400℃ and 600℃, the strength of the sample is only 0.13MPa and 0.15MPa, which cannot guarantee the full temperature range application of the sample. Comparative Example 2 replaces polyhydroxysilane with common silica sol. Unlike the silicon oxide nanoparticles inside the silica sol, polyhydroxysilane is a polymer ceramic precursor with Si-O-Si as the main molecular chain, and its network structure is more complex and has higher adhesion. In addition, after pyrolysis, it will generate Si-O short chains, which can react with boric acid at a lower temperature to form borosilicate glass, thereby increasing the strength of the sample at 600~1000℃. Therefore, for Comparative Example 2, since polyhydroxysilane is replaced with silica sol, the strength of the prepared samples at 400~1000℃ is relatively low. The role of silicon powder is to improve the high temperature stability of the overall binder, thereby ensuring that the sample has good strength at high temperatures. Therefore, for Comparative Example 3, since the formula does not contain silicon powder, when the sample is at high temperature, the generated borosilicate glass will soften, resulting in lower strength of the generated unfired zirconia fiber-based porous ceramic at 1200°C and 1400°C.

[0047]

[0048] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a calcined zirconia fiber-based porous ceramic, characterized in that: The steps include: (1) Adding boric acid and soluble chitosan to water, stirring until the boric acid and soluble chitosan are completely dissolved, then adding polyhydroxy silane to the solution, mixing evenly to obtain an organic-inorganic composite solution, wherein the mass ratio of water, boric acid, soluble chitosan and polyhydroxy silane is 100:(1-5):(4-15):(10-20); (2) adding silicon powder to the organic-inorganic composite solution, and ball milling and mixing to obtain a composite binder slurry, wherein the mass ratio of the silicon powder to the organic-inorganic composite solution is (1-5):100; (3) Adding zirconia fiber to the composite binder slurry, stirring evenly to form zirconia fiber slurry; (4) The zirconia fiber slurry is transferred to a mold and the mold is coated with a polyvinyl chloride film. Subsequently, the mold is transferred to a blast drying oven for heating to further promote the reaction between the soluble chitin, boric acid, and polyhydroxy silane. The polyvinyl chloride film is then removed and the excess water in the mold is drained by a vacuum filtration process to obtain a zirconia fiber-based porous ceramic wet blank. (5) The obtained zirconia fiber-based porous ceramic wet blank is dried in a forced air drying oven, and after demolding, the unfired zirconia fiber-based porous ceramic can be obtained.

2. The preparation method according to claim 1, characterized in that: The mass ratio of water, boric acid, soluble chitosan and polyhydroxy silane is 100: (3-5): (6-10): (15-20).

3. The preparation method according to claim 1, characterized in that: The mass ratio of the silicon powder and the organic-inorganic composite solution in step (2) is (1-3):

100.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the zirconium oxide fiber and the composite binder slurry in step (3) is (2-5):

100.

5. The preparation method according to claim 1, characterized in that: The temperature of the blast drying oven described in step (4) is 60-80°C, and the insulation time is 3-6 h.

6. The preparation method according to claim 1, characterized in that: The temperature of the blast drying oven described in step (5) is 80-90° C., and the insulation time is 6-8 h.

Citation Information

Patent Citations

  • Silicone rubber composition, preparation method and application thereof

    CN112480677A

  • High and low temperature resistant anti-vibration thermal insulation material and preparation method thereof

    CN115627007A